THE ROLE OF SPORTIVE ACTIVITIES IN CHILDREN'S PERSONALITY DEVELOPMENT - Cristian SANTA; Onela SANTA; Alin BACIU; Paul SZABO-ALEXI (Cluj University Press, 2015)
The athlete is the main subject of performance generator and is being defined by a large number of attributes, some of which are characteristic for achieving it. He can develop only if certain conditions are met both in terms of correlating interdependent attributes, qualities - skills and the environmental factors, social, material, teaching. The relationships between members of a community are subject to numerous factors such as: psychological peculiarities of the athletes, the general orientation, the reasons of the proposed activity, attitudes "built" in life and the society in which they live. There are a few things to note: first, the game strengthens a child physically, it embodies the taste of performance and the means to achieve it. Secondly, the game creates teamwork skills to synchronize their actions with those of others to achieve a common goal. A third, the game causes a good mood, cheerful, giving the people the ability to clear their heads and have fun giving more lust for life. Rolul jocurilor sportive in dezvoltarea personalitatii copiilor. Sportivul care este principalul subiect generator al performanţei este definit de un număr foarte mare de atribute dintre care unele sunt caracteristice pentru realizarea acesteia. El se poate dezvolta numai dacă sunt îndeplinite anumite condiţii atât în privinţa corelării interdependente a atributelor -însusiri, calităţi -aptitudini, cât şi a determinatelor ambientale, sociale, materiale, pedagogice. Relatiile care se stabilesc între membrii unei colectivităţi sunt condiţionate de numeroşi factori . Există câteva lucruri de remarcat: în primul rând, jocul fortifică un copil din punct de vedere fizic, îi imprimă gustul performanţelor precum şi mijloacele de a le realiza. În al doilea rând, jocul creează deprinderi pentru lucrul în echipă, pentru sincronizarea acţiunilor proprii cu ale altora, în vederea atingerii unui scop comun. Un al treilea rând, jocul provoacă o stare de bună dispoziţie, de voie bună, oferindu-i omului posibilitatea de a uita pentru un timp de toate celelalte şi de a se distra, dându-i parcă mai multă poftă de viaţă.  Cuvinte cheie: sportivi, jocuri sportive, relatiile de joc, organizare.